Al-Tawhid in relation to the economic order of microfinance institutions. Issue 4 (4th November 2014) - Alam Choudhury, Masudul; Abdullah, Rose
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to study the problems faced by microfinance institutions (MFIs) and relates it with Al-Tawhid to see the solutions. Design/methodology/approach – An exploratory method was used to examine various literature that discuss MFIs, the challenge issues growing in tandem with the growth of the microfinance sector and the economic order of MFIs and tries to link it to Al-Tawhid. Findings – The absence of Al-Tawhid concept in the practice of conventional MFIs caused the practices are not acceptable to Muslim micro entrepreneurs. Hence, the use of Al-Tawhid principles of contract suggested practices that are fair and free from elements of riba and gharar. It relates to the economics order by looking into the aims of providing finance up to reaching the consensus process or shuratic. Cash waqf is suggested as a source of fund for Islamic MFI for sustainability. Research limitations/implications – The findings need to be supported with empirical study to come up with suitable models. Practical implications – Alternative sustainable source of funds for the Islamic MFI is suggested. Social implications – Activating the cash waqf will involve the society in large to contribute to the economic development. The beneficiaries, such as the poor and needy, will be able to find a source of living and be actively involved in generating income activities. Originality/value – This paper highlights the cause of problems faced by conventional microfinance and relats the Al-Tawhid to overcome those problem conceptually.